Rac inactivation decreases cell adhesion strength in chronic myeloid leukaemia - Yang, Joan Xiaohui (2011)
Chronic myeloid leukemia is a hematological malignancy characterized by the reciprocal translocation between chromosomes 9 and 22, resulting in the expression of the constitutively active tyrosine kinase BCR-ABL. The treatment of chronic myeloid leukemia by the tyrosine kinase inhibitior, imatinib, has brought about much success in the field of medicine. However, the development of imatinib resistance has led researchers to look for alternative treatments in an attempt to cure the disease. Targeting the downstream signaling pathways of BCR-ABL is a potential strategy. Previous studies have shown that the combination of imatinib and Rac inhibitors resulted in a synergistic apoptotic effect on K562 cells as compared to single arm drug treatment. It has also been confirmed that the Rac inhibitors led to a decrease in the expression of activated Rac1. Since the adhesion of cells to its extracellular matrix (ECM) play an important role in many cellular processes including migration, this project serves to find this relationship between the inhibition of Rac and the adhesion properties of CML cells. In this study, using fibronectin as a substrate, we have demonstrated that the adhesion strength of K562 cells treated with different Rac inhibitors was decreased in comparison to untreated control cells. We conclude that with the inhibition of Rac, there is a decrease in the adhesive properties of the cells. The trend of adhesive energy of the different conditions of drug treatment was also quantitatively validated by the percentage of cells adhered to fibronectin.